Analysis of e-waste recycling behavior based on survey at a Midwestern US University. (15th March 2020) - Arain, A.L.; Pummill, R.; Adu-Brimpong, J.; Becker, S.; Green, M.; Ilardi, M.; Van Dam, E.; Neitzel, R.L.
Highlights: Consumer behaviors are critical to managing and reducing e-waste. Faculty, students, and staff at a Midwestern University surveyed regarding e-waste. Cost, knowledge, and access to recycling affect consumers choice to recycle. Increased consumer knowledge should be paired with free or low-cost e-waste recycling options. Abstract: The United States lacks a set of unified electronic waste recycling laws, contributing in part to the observed low rate of e-waste recycling behaviors among consumers. Individual factors of consumers contributing to the low recycling rates are not well understood. The objective of this study was to evaluate consumer behaviors, including barriers, surrounding e-waste recycling at a large Midwestern university in the United States. A survey was administered to faculty, graduate students, undergraduate students, and staff to determine their personal recycling habits, knowledge, and beliefs. The results indicate that free access to disposal, lack of consumer knowledge about products and disposal sites, and access to a recycling facility within a reasonable distance are all important factors in consumer decisions. Policy-makers and waste management professionals should focus on promotion of e-waste recycling behaviors through increased access to free or low-cost recycling as well as through the creation of recycling incentives.